2002
DOI: 10.4141/a01-080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet and parity on meal patterns of lactating dairy cows

Abstract: . 2002. Effect of diet and parity on meal patterns of lactating dairy cows. Can J. Anim. Sci. 82: 215-223. Four multiparous and four primiparous lactating dairy cows housed in stalls were used in a double 4 × 4 Latin square to determine the effect of parity and diet on meal patterns. Cows were fed one of four diets: three total mixed rations containing 40, 50, or 60% barley silage on a dry matter (DM) basis, and a diet in which forage and concentrate were allocated separately (SI) containing 50% concentrate. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 27 publications
8
25
5
Order By: Relevance
“…In dairy cows, DeVries et al (2007) reported that cows consuming a 50.7% forage diet spent more time eating than those fed a 62.3% forage diet. Our results concur with reports that lactating cows consumed concentrate faster than the forage portion of their ration (Beauchemin, Eriksen, Nørgaard, & Rode, 2008;Beauchemin, Maekawa, & Christensen, 2002). McClure, Van Keuren, and Althouse (1994) pointed out that DMI decreases with increase in forage NDF in the lamb's diet.…”
Section: Discussionsupporting
confidence: 92%
“…In dairy cows, DeVries et al (2007) reported that cows consuming a 50.7% forage diet spent more time eating than those fed a 62.3% forage diet. Our results concur with reports that lactating cows consumed concentrate faster than the forage portion of their ration (Beauchemin, Eriksen, Nørgaard, & Rode, 2008;Beauchemin, Maekawa, & Christensen, 2002). McClure, Van Keuren, and Althouse (1994) pointed out that DMI decreases with increase in forage NDF in the lamb's diet.…”
Section: Discussionsupporting
confidence: 92%
“…Meal size, meal length and the interval between meals were similar between multiparous and primiparous cows. Similarly, Beauchemin, Maekawa, and Christensen () reported that meal interval did not differ between parity in mid‐lactation, but primiparous cows consumed less feed per meal compared with multiparous cows. Multiparous cows had longer ( p = .03) interval between ruminating bouts compared with primiparous cows, which might be associated with more efficient rumination activity in older cows than younger cows.…”
Section: Resultsmentioning
confidence: 92%
“…In competitive and noncompetitive environments, feeding activity increases after the delivery of fresh feed (Philips and Rind, 2001;Beauchemin et al, 2002;DeVries et al, 2003). Pushing the feed toward the animal results in an increase in feeding activity (DeVries et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dairy cows fed a TMR are normally provided with fresh feed only once or twice daily. The increase in feeding behavior after feed delivery will, therefore, result in variation in feeding behavior throughout the day (Beauchemin et al, 2002;DeVries et al, 2003). This variation in feeding behavior contributes to variation in pH, VFA, and ammonia in the rumen within 24 h (Keunen et al, 2002;Kononoff and Heinrichs, 2003).…”
Section: Introductionmentioning
confidence: 99%